Wheat bran extract alters colonic fermentation and microbial composition, but does not affect faecal water toxicity: a randomised controlled trial in healthy subjects - Windey, Karen; De Preter, Vicky; Huys, Geert; Broekaert, Willem F.; Delcour, Jan A.; Louat, Thierry; Herman, Jean; Verbeke, Kristin (British journal of nutrition, 2015)
Wheat bran extract (WBE), containing arabinoxylan-oligosaccharides that are potential prebiotic substrates, has been shown to modify bacterial colonic fermentation in human subjects and to beneficially affect the development of colorectal cancer (CRC) in rats. However, it is unclear whether these changes in fermentation are able to reduce the risk of developing CRC in humans. The aim of the present study was to evaluate the effects of WBE on the markers of CRC risk in healthy volunteers, and to correlate these effects with colonic fermentation. A total of twenty healthy subjects were enrolled in a double-blind, cross-over, randomised, controlled trial in which the subjects ingested WBE (10 g/d) or placebo (maltodextrin, 10 g/d) for 3 weeks, separated by a 3-week washout period. At the end of each study period, colonic handling of NH3 was evaluated using the biomarker lactose[15N, 15N′]ureide, colonic fermentation was characterised through a metabolomics approach, and the predominant microbial composition was analysed using denaturing gradient gel electrophoresis. As markers of CRC risk, faecal water genotoxicity was determined using the comet assay and faecal water cytotoxicity using a colorimetric cell viability assay. Intake of WBE induced a shift from urinary to faecal 15N excretion, indicating a stimulation of colonic bacterial activity and/or growth. Microbial analysis revealed a selective stimulation of Bifidobacterium adolescentis. In addition, WBE altered the colonic fermentation pattern and significantly reduced colonic protein fermentation compared with the run-in period. However, faecal water cytotoxicity and genotoxicity were not affected. Although intake of WBE clearly affected colonic fermentation and changed the composition of the microbiota, these changes were not associated with the changes in the markers of CRC risk.